The method of determining the amount of information considering the factor of aging - Юдін, О. К.; Стрельбіцький, М. А. (Science-based technologies, 2017)
At the modernization, stage of information and telecommunication systems of the national security subjects of Ukraine there is a problem of information reliability when ones use the sharing data. For estimating the probability of violation of the information, properties need to determine the quantity of information provided into component of the system. The article presents the method of determining the quantity of information that flows into the telecommunications system with factor of aging.